1996
DOI: 10.1073/pnas.93.13.6687
|View full text |Cite
|
Sign up to set email alerts
|

An alpha-mercaptoacrylic acid derivative is a selective nonpeptide cell-permeable calpain inhibitor and is neuroprotective.

Abstract: Overactivation of calcium-activated neutral protease (calpain) has been implicated in the pathophysiology of several degenerative conditions, including stroke, myocardial ischemia, neuromuscular degeneration, and cataract formation. Alpha-mercaptoacrylate derivatives (exemplified by PD150606), with potent and selective inhibitory actions against calpain, have been identified. PD150606 exhibits the following characteristics: (i) K; values for ,u-and m-calpains of 0.21 ,uM and 0.37 ,IM, respectively, (ii) high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
2
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(186 citation statements)
references
References 38 publications
9
171
2
4
Order By: Relevance
“…The mammalian cal- (45).) To confirm the possibility that ras down-regulates Beclin-1 in a calpain-dependent manner we treated the ras-transformed cells with PD150606, a small molecule calpain inhibitor that is structurally unrelated to ALLM (46). We found that, similar to what was observed with ALLM, treatment with PD150606 does result in the up-regulation of Beclin-1 in these cells (Fig.…”
Section: Oncogenic Ras Promotes the Degradation Of Beclin-1 In Intestsupporting
confidence: 53%
“…The mammalian cal- (45).) To confirm the possibility that ras down-regulates Beclin-1 in a calpain-dependent manner we treated the ras-transformed cells with PD150606, a small molecule calpain inhibitor that is structurally unrelated to ALLM (46). We found that, similar to what was observed with ALLM, treatment with PD150606 does result in the up-regulation of Beclin-1 in these cells (Fig.…”
Section: Oncogenic Ras Promotes the Degradation Of Beclin-1 In Intestsupporting
confidence: 53%
“…Extracellular drug application. Stock solutions were prepared in DMSO or H 2 O and were dissolved before use in 2 ml saline in the static bath and mixed thoroughly to obtain final concentrations of 100 M N-acethyl-Lleucyl-L-leucyl-L-norleucinal (N-acetyl-Leu-Leu-Norleu-al, calpain inhibitor I, ALLN, AcLLnL-CHO) (Sigma Aldrich); 100 M 3-(4-iodophenyl)-2-mercapto-(Z)-2-propenoic acid (PD 150606) inhibitor, which specifically blocks the Ca 2ϩ binding site of calpain and noncompetitively blocks calpain activity by binding to the Ca 2ϩ -binding domain of calpain (Wang et al, 1996a); 100 M control 3-phenyl-2-mercaptopropionic acid (PD 145305) (Calbiochem); 100 M carbobenzoxyvalinyl-phenylalaninal (MDL-28170) (Enzo Life Sciences), inhibitor of calpain I and II; 50 M 1,2-bis(o-aminophenoxy)ethane-N, N,NЈ,NЈ-tetraacetic acid tetra(acetoxymethyl) ester (BAPTA-AM) (Calbiochem); and tetra(acetoxymethylester)-AM (EGTA-AM) (Invitrogen) at DMSO concentration Ͻ0.1-0.2% (v/v). To load cells with the Ca 2ϩ buffer, EGTA-AM plus 1% Pluronic F-127 was applied at final concentration of 50 M in saline containing 0.2% DMSO for 30 min, followed by an additional 30 min incubation to permit complete de-esterification (Zhong and Zucker, 2004).…”
Section: Electrophysiologymentioning
confidence: 99%
“…Therefore, we sought alternative mechanisms that could cause hysteresis in activation of calcineurin. One possibility is activation of the Ca 2ϩ -dependent protease calpain, which partially cleaves the regulatory domain of calcineurin to give constitutively active phosphatase (Wang et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The possible implication of calpain in ATRA-induced IkBa degradation was tested by using a calpain inhibitor, PD150606, which blocks its calcium-binding site (Wang et al, 1996). Addition of this inhibitor to ATRA-treated cells resulted in an increased level of IkBa expression as compared to its expression in cells treated with ATRA alone (Figure 2d and e), while the inactive analogue, PD145305, had no effect (Figure 2e).…”
Section: Inhibition Of Calpain But Not Of Ikk Activity Impairs Atra-imentioning
confidence: 99%